1993
DOI: 10.1002/gcc.2870060409
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐mesenchymal transitions during cell culture of primary thyroid tumors?

Abstract: Fibroblast contamination of epithelial tumor cell cultures is of great concern when examining tumor cells in vitro for specific biochemical and cytogenetic changes. The observations of normal karyotypes in thyroid tumor cell cultures have raised the concern of whether residual tissue fibroblasts might obscure the cytogenetic analysis of transformed epithelial cells. We have characterized early passaged thyroid tumor cells to examine the proportions of epithelial and fibroblastic cell types. Cells were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Epithelial cells grown on plastic dishes often aberrantly express vimentin (Fig. 1B, top row) albeit at a low level compared to the usual epithelial keratins (27). When grown in 3D, vimentin is not expressed in the P69 subline, akin to expression patterns in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Epithelial cells grown on plastic dishes often aberrantly express vimentin (Fig. 1B, top row) albeit at a low level compared to the usual epithelial keratins (27). When grown in 3D, vimentin is not expressed in the P69 subline, akin to expression patterns in vivo (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The persistence of cytokeratin in the cytoplasm of the newly formed mesenchyme-like cells points strongly that their origin is follicular epithelium, since there is no keratin expression in mesenchymal cells surrounding the follicles in situ. Also, Hermann et al [16] have shown similar morphological findings in thyroid neoplasm. The results suggested that there is a unique cell type intermediate between epithelial and mesenchymal phenotypes that exhibit reactivity with antibodies to cytokeratin, thyroglobulin, and vimentin.…”
Section: Discussionmentioning
confidence: 62%
“…The spindle-cell metaplastic transformation of follicular epithelium is not at all surprising if we consider that both normal and neoplastic thyroid follicular cells in vitro may undergo an epithelial-mesenchymal transition with a fibroblastic-like appearance characterized by an acquisition of vimentin expression accompanied by a concurrent variable loss of cytokeratin [2,3]. The present case contributes to widen the spectrum of the spindle-cell lesions, which can be encountered in diagnostic practice of thyroid pathology.…”
mentioning
confidence: 69%